(untitled) (International Journal of Business, Economics and Management, 2017)
In general the study of internationalization process of companies from Latin America is scarce compared with companies from Europe and USA. Likewise the study of state ownership in the region is scarce. In this regard, the main aim of this paper is analyze the internationalization patterns of the main state multilatinas: PEMEX (Mexico), PETROBRAS (Brazil) and PDVSA (Venezuela). Considering the interpretation of the main internationalization theories as: Eclectic paradigm and Uppsala model, a multi-case method was carried out in order to fulfill the purpose of this paper. The main results suggest an integrated operation, combined with innovation and technological development is used by the studied companies. Likewise, the three companies follow similar internationalization patterns as exports, joint ventures and foreign direct investment. The main difference is the place where they go abroad, PEMEX mainly focus its international operations in Europe and USA, PDVSA, go mainly USA and Asia and PETROBRAS go to Latin America and Africa.